Ordering the Preference Hierarchies for Internal Finance, Bank Loans, Bond and Share Issues - Leo de Haan; Jeroen Hinloopen (Tinbergen Institute, 2002)
We estimate the incremental financing decision for a sample of some 150Dutch companies for the years 1984 through 1997, thereby distinguishinginternal finance and three types of external finance: bank borrowing, bondissues and share issues. First, we estimate a multinomial logit model whichconfirms several predictions of both the static trade-off theory and thepecking-order theory as to the determinants of financing choices. Next, weuse ordered probit models to determine which financing hierarchy fits thedata best. The results suggest that Dutch firms have a most-preferredfinancing hierarchy: (i) internal finance, (ii) bank loans, (iii) shareissues, (iv) bonds issues.
Keywords: G32; C25; 330; corporate finance; discrete choice models; ordered financing hierarchies; Betriebliche Finanzwirtschaft; Kapitalstruktur; Entscheidung; Schätzung; Niederlande